Method for manufacturing a storage battery

The formation of tightly adhered multi-layered layers through injection technology and electrostatic assist technology solves the problems caused by long solvent volatility and reduced adhesive, improves the productivity and performance of all-solid batteries, and achieves fast charging and efficient battery performance.

CN112585798BActive Publication Date: 2024-12-31MTEK SMART
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN201980054852.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-08-21
Filing Date
2019-08-13
Publication Date
2024-12-31
Estimated Expiration
2039-08-13

AI Technical Summary

Technical Problem

In the existing all-solid battery manufacturing methods, the solvent volatility time is long, the production line speed is limited, the particle precipitation problem after the binder is reduced, and the interface adhesion is insufficient, resulting in long charging time and poor battery performance.

Method used

The spray head or particle generator is used to impact spray the slurry composed of active substances and electrolyte particles and solvents to form a tightly adhered multi-layer layer, reduce the use of binder, and use pulse jet and electrostatic assistive technologies to improve adhesion efficiency and increase Interface surface area and adhesion.

Benefits of technology

Significantly shortens charging time, improves battery productivity, reduces sintered residual carbon, enhances the adhesion between the electrode and electrolyte layer interface, and improves battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112585798B_ABST
    Figure CN112585798B_ABST
Patent Text Reader

Abstract

Increase the cross-section of the collector and active material or electrolyte of the all-solid battery, or the surface area of ​​the cross-section of the active material and the electrolyte, improve the adhesion, and reduce the resistance. In addition, eliminate or reduce the residual carbon caused by the binder to improve the battery performance. By impacting and attaching the slurry composed of the electrode active material and the solvent, and the slurry composed of the electrolyte particles and the solvent to the object with impact force, a high-density layer is formed to improve the adhesion. By not using or using only a small amount of binder, the residual carbon is eliminated or reduced, thereby improving the battery performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for manufacturing an all-solid-state battery, which is composed of a laminate formed by forming a positive electrode layer, an electrolyte layer, and a negative electrode layer by forming a slurry of particles containing an active material, etc. to form electrode layers at both poles, forming a slurry of electrolyte particles to form an electrolyte layer, and then laminating a positive electrode layer, an electrolyte layer, and a negative electrode layer. The detailed description mainly describes the method for manufacturing an all-solid-state battery, which is applicable to all storage batteries and can also be applied to metal-air batteries, etc., which are expected to become next-generation batteries.

[0002] Although the increase in mobile and electric vehicles requires rechargeable batteries including lithium batteries to be quickly charged, it still takes tens of minutes to charge electric vehicles. Considering the length of time and safety risks, the technology currently being developed is to change the electrolyte from liquid to solid to shorten the 80% charging time to a few minutes.

[0003] Patent document 1 proposes a method for manufacturing a layered structure of a solid electrolyte layer, a positive electrode active material layer, and a negative electrode active material layer of an all-solid-state battery, wherein a slurry containing materials constituting the layered structure is modulated to form a raw sheet, the raw sheet is integrally formed with a sheet having projections and depressions that disappear by heating, thereby forming projections and depressions on the surface of the raw sheet, the integrally formed raw sheet and sheet are then heated to make the sheet disappear, the raw sheet is sintered, and finally projections and depressions are formed on the substrate while forming electrodes.

[0004] Patent document 2 proposes a polyvinyl alcohol acetal resin that can be degreased in a short time under low temperature environment when forming electrode layers and electrolyte layers of all-solid batteries. Specifically, it is used for electrode slurry composed of active material particles, solvents and binders for lamination, or electrolyte slurry composed of electrolyte particles, solvents and binders. More specifically, the solid electrolyte slurry and the negative or positive electrode slurry are coated on the support layer of the PET film after demolding, and the PET film is peeled off after drying at 80°C for 30 minutes, and then the negative and positive active material layers are sandwiched on the electrolyte layer, and heated and pressed at 80°C and 10KN to obtain a laminate, and then a conductive paste containing acrylic resin is coated on a stainless steel plate to form a collector, and finally sintered at below 400°C in a nitrogen environment to degrease the binder.

[0005] In the method of patent document 1, it is ideal to coat the active material slurry or electrolyte slurry on a sheet of polyvinyl alcohol or the like having projections and depressions to increase the contact area between the active material layer and the electrolyte layer. However, there is a problem that the resin component takes a long time to disappear at high temperatures (for example, 50 hours at 700°C).

[0006] In addition, in Patent Document 2, in order to allow the solvent component of the slurry to volatilize within 30 minutes at 80°C, even if the speed of the lithium-ion battery production line is adjusted to the current 100 m / min, the length of the production line still becomes very long, so there is a problem that the production line speed has to be reduced.

[0007] In any of the methods, if the binder of the slurry is eliminated or reduced, precipitation of particles occurs in a general circulation device, and coating cannot be performed using a die head used in forming electrodes for lithium batteries.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. WO2012 / 053359

[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 2014-212022 Summary of the invention

[0012] Problems to be solved by the invention

[0013] The present invention aims to improve productivity, eliminate or minimize residual carbon generated when a laminated body to be fired is fired, and improve the adhesion of the interfaces of each laminated body. In addition, by expanding the surface area of ​​the interface of the electrode layer or the electrolyte layer, the interface resistance is reduced and the battery performance is improved.

[0014] The solid electrolyte particles in the present invention are not limited to the type of sulfide or oxide particles, and are not limited to the type of active material particles for positive or negative electrodes.

[0015] For example, when the electrolyte is a sulfide such as LPS, the positive electrode can be lithium sulfide (Li2S) particles or sulfur (S8), and the negative electrode is particles of graphite or silicon.

[0016] Technical solutions to solve problems

[0017] The present invention is completed to solve the above-mentioned problems. The purpose of the present invention is to be able to granulate a slurry consisting of particles of active materials and electrolytes of positive and negative electrodes and a solvent, or a slurry consisting of particles, solvents and a binder as a binder of particles using a nozzle or a particle generating device whenever a high-quality all-solid-state battery is manufactured, and adjust the speed of the particles to a desired speed so that they impact an object with impact force, so that the particles are tightly and strongly attached to the object after the solvent evaporates.

[0018] The so-called object refers to the positive electrode layer, the negative electrode layer, the electrolyte layer and the current collector. When the electrode slurry particles are attached, the object refers to the current collector or the electrolyte layer, and when the electrolyte slurry particles are attached, the object mainly refers to the positive electrode and the negative electrode layer. When the electrolyte particles are attached to the current collector together with the particles of the active material of the positive electrode and the negative electrode, the object also includes the electrode.

[0019] The present invention provides a method for manufacturing an all-solid-state battery formed by stacking electrode layers and electrolyte layers of the all-solid-state battery, characterized in that the interface between the electrode layer and the electrolyte layer is formed by impact spraying an electrode slurry composed of at least electrode active material particles and a solvent, or an electrolyte slurry composed of at least electrolyte particles and a solvent.

[0020] The present invention provides a method for manufacturing an all-solid-state battery by coating an electrode slurry on a collector to form an electrode, characterized in that a slurry consisting of at least an electrode active material and a solvent, and a slurry consisting of at least electrolyte particles and a solvent are alternately impact-sprayed to form a multilayer stack.

[0021] The present invention provides a method for manufacturing an all-solid-state battery, characterized in that the electrode slurry or electrolyte slurry is granulated by a particle generating device or a fine particle generating device, and the particles or particle groups are moved and impacted and attached to at least one of the collector, electrode layer, and electrolyte layer as the object with a pressure difference.

[0022] The present invention provides a method for manufacturing an all-solid-state battery, characterized in that the electrode slurry or the electrolyte slurry contains a binder.

[0023] The present invention provides a method for manufacturing an all-solid-state battery, characterized in that at least the surface of the active material particles or the electrolyte particles is previously covered with a binder in a thin film manner, and the solvent of the slurry is a poor solvent for the binder.

[0024] The present invention provides a method for manufacturing an all-solid-state battery, characterized in that electrode slurry or electrolyte slurry is formed into microparticles and then attached to the object, and more than 95% of the solvent is evaporated within at least 2 seconds after the object is heated and the microparticles are attached.

[0025] The present invention provides a method for manufacturing an all-solid-state battery as described in claims 1 to 7, characterized in that the spraying or movement of particles is performed in a pulse mode of 1 to 1000 Hz (Hertz).

[0026] In the present invention, the weight ratio of the binder amount in each slurry is preferably less than 10% of the weight of the total solid content, especially when sintering is performed in the subsequent process, and preferably less than 2% from the viewpoint of further reducing residual carbon. By applying a potential difference between the object and the slurry, or between the fine particles granulated by a nozzle (spray), static electricity can be used to assist the attachment of fine particles. It is particularly effective for attaching submicron or smaller ultrafine particles. In order to charge the sprayed particles, the above-mentioned binder or solvent should be selected to be easily charged by static electricity.

[0027] According to the manufacturing method of the all-solid battery of the present invention, the jet particles are impacted on the object with impact force to form an ultra-fine particle group. Furthermore, the interface of the electrode can be easily formed into fine concave-convex shapes, or concave-convex shapes of a desired size as required, thereby increasing the contact area with the electrolyte layer, and enhancing adhesion through the anchoring effect, and minimizing the interface resistance.

[0028] In addition, in the present invention, the object and the nozzle can be relatively moved, and the positive electrode layer, the electrolyte layer, and the negative electrode layer can be formed into a granular manner by spraying the electrode slurry or the electrolyte slurry to form a laminated body. In addition, for the positive electrode layer, the electrolyte layer, and the negative electrode layer, the above-mentioned slurry is formed by methods such as die coating, roller coating, curtain coating, and screen coating to increase the processing speed, and only the desired slurry, solvent, and a very small amount of binder solution of the solid component that forms the interface with the positive electrode layer, the electrolyte layer, the negative electrode layer, or the collector are granulated and attached with impact to form a laminated body.

[0029] In the present invention, the electrode is not limited to a single slurry formed by mixing various types of particles, and it can also be formed by making various types of different slurries and correspondingly using multiple nozzles. Different specific gravities and particle sizes can be used. For example, electrode particles and electrolyte particles can be mixed to form a slurry that does not contain or contains only a very small amount of binder. Regardless of the uniformity of the mixing, the particles with a heavy specific gravity will settle over time or immediately, and their dispersion state will also change. It is also possible to make a slurry composed of electrode particles and a slurry composed of electrolyte particles, respectively forming a required proportion of the injection amount, and overlapping them in a desired manner in a film, such as alternately stacking, and finally obtaining a laminate of an ideal electrode. In addition, the method is effective for the desired distribution and lamination of conductive aids such as active materials, carbon particles, and carbon nanofibers, and the active materials have a large difference in the ratio per unit volume and have different specific gravities and particle sizes. The conductive aid is too small or too large in each unit volume in the electrode layer. It will affect the performance, so compared with the method of coating it with the mixed slurry of the active material, its performance can be greatly improved.

[0030] In addition, the conductive additive can further reduce the solid content concentration of the slurry. For example, in a slurry state below 10%, a thin film is formed and layered so that it is entangled with the active material particles. The more layers are layered, the more uniform the coating amount per unit area will be, thereby improving battery performance.

[0031] In addition, the present invention can also give the silicon particles on the negative electrode a binder or adhesive with strong binding force and expandable and contractible, so as to effectively prevent the performance degradation caused by the expansion and contraction of the silicon particles. That is, the slurry composed of silicon particles and the strong binder solution or emulsion are formed into particles and layered with their own nozzles, so that the bonding particles are partially attached to the surface of the silicon particles and finally form an electrode layer. In order to form the binder into a jet or fine particles and move and attach to a part or the whole of the surface of the silicon particles, it is most appropriate to select a pulse with impact force. It can also be carried out by adding carbon particles to the binder solution or binder emulsion and making it into a slurry.

[0032] In addition, the object can be heated. The heating temperature is preferably 30 to 150 degrees Celsius. Heating the object can evaporate the solvent component of the granulated slurry while it is in contact with and soaked in the object. It is preferred that the time for 95% of the solvent to evaporate is within 2 seconds, and more preferably within 1 second. If the time is longer than 2 seconds, the particle group with impact force and high density accumulation will become loose due to the solvent. If the solvent evaporates while impacting, the spray particles and the like will be easily scattered, and the binder will be easily boiled.

[0033] In the present invention, when the slurry is sprayed to form particles and attached to the object, it can be done in a pulsed manner, which can increase the impact force. In particular, the air spraying method known as dual-fluid spraying can be used in the industry. Since there is a lot of air around the sprayed particles, such as 400 or even 600 times, the particles that reach the object later will be pushed back into the air on the object, which not only loses the impact force, but also has a very serious impact on the attachment efficiency of the particles. When the slurry and air are sprayed in a pulsed manner, the air compressed between the sprayed particle groups will diffuse, so that only those particles with directionality will move and attach.

[0034] Therefore, the adhesion efficiency is 95% or more, compared with 30 to 50% in the conventional spraying method, and is economical.

[0035] By using the pulse spraying method, the amount of conductive additive applied can be reduced to less than one tenth of that in the conventional spraying method, which is very convenient for adjusting the ratio with the active material.

[0036] Effects of the Invention

[0037] As described above, the present invention can produce high-performance all-solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a schematic diagram showing the spraying of active material onto an object (current collector) according to an embodiment of the present invention.

[0039] Figure 2 This is a schematic diagram showing that different types of particles (such as a conductive auxiliary agent) are sprayed onto active material particles attached to an object according to an embodiment of the present invention.

[0040] Figure 3 This is a cross-sectional view showing a laminate of two types of particles according to an embodiment of the present invention.

[0041] Figure 4 It is a cross-sectional view showing a current collector, a positive electrode layer, an electrolyte layer, a negative electrode layer, and a current collector which are stacked according to an embodiment of the present invention.

[0042] Figure 5 It is a cross-sectional view after the electrode slurry is sprayed onto the object (current collector, electrolyte layer) according to the embodiment of the present invention.

[0043] Figure 6 It is a cross-sectional view after spraying onto the object (electrolyte layer, electrode layer) according to the embodiment of the present invention.

[0044] Figure 7 It is a cross-sectional view after spraying onto the object (electrolyte layer) according to the embodiment of the present invention.

[0045] Figure 8 It shows a cross-sectional view after different types of materials are alternately ejected in a pulse manner with a time difference to form a stacked layer according to an embodiment of the present invention. DETAILED DESCRIPTION

[0046] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be noted that the following embodiments are only examples for easy understanding of the invention, and those skilled in the art may make feasible additions, replacements and modifications without departing from the scope of the technical concept of the present invention, which are all included in the scope of the present invention.

[0047] The accompanying drawings show preferred embodiments of the present invention.

[0048] exist Figure 1In the process, a slurry consisting of active material particles for an electrode and a solvent, or a slurry consisting of an active material, a solvent and a binder is sprayed from a nozzle 21 onto a current collector 1 as an object, so that the active material spray particles 2 are attached to the current collector 1 to form active material particles 2'. The active material particles 2' may be particles formed by covering active material particles with electrolyte materials. The spraying may be performed in a pulsed manner, and the particles may be attached to the current collector with impact force at a high speed, so that the adhesion may be improved. In order to make the sprayed particles 2 have impact force, the distance between the object and the nozzle may be as close as possible, for example, it may be controlled to be less than 70 mm. In addition, it may be achieved by using a spraying form of a two-fluid nozzle with a narrow spraying angle of less than 30 degrees, and by pulse spraying at an air pressure of 0.15 to 0.3 MPa. Considering productivity, the number of pulses per second is preferably above 10 Hz.

[0049] The shorter the distance and the narrower the angle of the spray pattern, the greater the impact force.

[0050] Figure 2 It means that Figure 1 A different type of slurry (eg, a slurry composed of electrolyte particles) is sprayed around or on the top of the active material particles 2' with a thin film (eg, 1 layer) attached thereto by a nozzle 22, and the slurry is dispersed on the thin film. Figure 1 The active material spraying from the nozzle 21 and the electrolyte spraying from the nozzle 22 can be alternately stacked on the thin film. Instead of the electrolyte particles, a conductive aid selected from any one of carbon particles, carbon fibers, and carbon nanotubes, or a solution and slurry composed of conductive aids such as lithium iodide, and a slurry of a mixture of electrode active materials or electrolyte particles added thereto can be used, and it is sprayed from the nozzle 22 to complete the attachment of the sprayed particles 3. The larger the surface area of ​​the porous carbon or nanocarbon of the conductive aid, the better, for example, the surface area in the BET diagram is more than 2000 square meters per gram, and more preferably more than 3500 square meters. If this is the case, the electrode performance can be improved by pre-sealing sulfur and active materials in the positive electrode in nano-scale pores, and nano-scale silicon in the negative electrode.

[0051] Figure 3 This is a diagram after alternately stacking electrode active material particles 2' and electrolyte particles 3', and the weight ratio per unit area can be freely selected, especially when the pulse spraying is performed, the ratio is easy to adjust. In addition, other nozzles can be used to disperse and apply the required amount of conductive additive around the electrode active material and make it adhere.

[0052] Figure 4The figure shows a laminated body for a solid-state battery formed by laminating a positive electrode layer 11 and a negative electrode layer 13 on both sides of an electrolyte layer 12, and sandwiching the electrode layers 11 and 13 between current collectors 1 and 10 and heating or pressing at room temperature. Generally, the current collector uses aluminum foil for the positive electrode and copper foil for the negative electrode, but there is no particular limitation, and a stainless steel sheet or the like can be used depending on the type of active material or electrolyte.

[0053] Figure 5 The figure shows that the electrolyte slurry is sprayed alternately from the nozzle 24 on the positive electrode collector 1, the positive electrode layer 11, and the electrolyte layer 12, and the negative electrode active material slurry is sprayed from the nozzle 23 to form a negative electrode layer on the negative electrode collector, and the rollers 31, 31' are used for pressing. During the formal pressing in the subsequent process, the pressing pressure can be almost zero or low. The rollers can also be heated, or the collector, the electrode layer, and the electrolyte layer can be preheated to promote the volatilization of the solvent rich in the sprayed particles 4, 5.

[0054] Figure 6 The figure shows that the electrolyte or electrode active material slurry is sprayed at the interface between the electrolyte membrane layer 12 and the negative electrode layer 13 by the nozzle 25. By spraying the solvent, the binder at each interface is instantly swollen, thereby improving the close adhesion of the interface. The rollers 31, 31' are moved without applying pressure or pressing. The load, diameter, and number of the pressing rollers are not limited.

[0055] Figure 7 The figure shows that the electrolyte layer slurry or solvent is sprayed on the electrolyte layers formed on both sides of the flexible current collector, the positive electrode layer, and the negative electrode layer. The effect is the same as the above content.

[0056] Figure 8 The figure shows that the negative electrode active material slurry is pulse-sprayed on the negative electrode collector 10 by the nozzle 23 to form a spray particle group 7. On the other hand, the electrolyte slurry is pulse-sprayed from the nozzle 24 to form a spray particle group 8, and each spray particle group is alternately layered on the negative electrode collector. When multiple layers are layered on the film, the effect is better.

[0057] Likewise, the positive electrode active material and the electrolyte slurry may be alternately layered on the positive electrode current collector. Furthermore, a nozzle (not shown) may be added to alternately spray the conductive auxiliary agent slurry in a pulsed manner and in a small amount with the nozzle 23 or 24 .

[0058] In the present invention, in order to improve productivity, for an object with a width of 1500 mm, a nozzle group can be formed to spray with impact force by disposing one type of slurry with 100 to 200 nozzles per layer along the moving direction of the object in about one or more rows. If necessary, the nozzle group can be moved back and forth (shaken) at a speed of 15 mm along the nozzle arrangement direction so that the 15 mm pattern fully overlaps without leaving a gap. In addition, the nozzles of the necessary number of types of slurries or the required number of layers can be arranged to meet the speed requirements.

[0059] If the structure of the nozzle is to be simplified, a groove can be formed every 10 mm in the width direction of the wide roller in Japanese Patent Publication No. 08-309269 developed by the inventor. When the roller rotates, the slurry filled in the groove is granulated with compressed gas and attached to the object. The speed of the object can theoretically be more than 100 meters per minute. The roller device can be arranged perpendicular to the moving direction of the object according to the number of slurry portions or the number of layers.

[0060] In addition, Japanese Patent Laid-Open No. 06-86956 developed by the inventor can also be used. The slurry can be filled in countless holes (such as holes with a diameter of 150 microns) that penetrate a cylindrical screen or seamless belt that is wider than the width of the object, and liquefied gas or compressed gas is blown out at a position opposite to the object to granulate it into fine particles, thereby evenly adhering to the entire surface of the object. If a commercially available rotary screen for screen printing is used, it is economical. In addition, if holes with a diameter of 0.3 mm or 0.5 mm are staggered at a spacing of 1.5 mm on a cylindrical tube that is wider than the object, the same effect can be obtained.

[0061] In the above two methods, it is preferred to control the distance between the granulation blowing position and the object to be less than 70 mm, because this can improve the impact effect.

[0062] In addition, the above two methods are performed by changing the rotation speed while being compatible with the volumetric supply method, so no expensive pumps or controllers are required. At the same time, this structure is an extension of the Roll to Roll of a roll coater or screen printer and is manufacturable, so a part can be further modified to make it applicable to the conventional lithium battery electrode production line.

[0063] There is a method of using pressure difference to make slurry into particles and move them. Among them, the granulation can be made by inkjet, or by a disc or bell-shaped rotating atomizer used in the general coating field. In addition, it is also possible to use a bubbler or ultrasonic atomizer, and to make it finer by installing a roller that rotates the jet at a close distance. The granulated particle group can be moved by the carrier gas and attached to the object by differential pressure.

[0064] If the movement is performed in a pulsed manner, the adhesion efficiency and impact are improved, which is preferable.

[0065] Industrial Applicability

[0066] According to the present invention, a laminate composed of an electrolyte, an electrode, and a current collector for an all-solid-state battery having low interface resistance and high adhesion can be produced with high quality.

[0067] Explanation of symbols

[0068] 1. Positive electrode collector

[0069] 2.4 Electrode active material injection particles

[0070] 2' Electrode active material

[0071] 3.5 Electrolyte injection particles

[0072] 3' Electrolyte particles

[0073] 6 Solvent and other spray particles

[0074] 7 Electrode active material injection particle group

[0075] 8 Electrolyte injection particle group

[0076] 10 Negative electrode collector

[0077] 11. Positive electrode layer

[0078] 12 Electrolyte layer

[0079] 13 Negative electrode layer

[0080] 21, 22, 23, 24, 25 nozzles

[0081] 31, 31' roller.

Claims

1. A method for manufacturing a storage battery, characterized in that: When forming an electrode on an object, a plurality of nozzles independently spraying a plurality of different types of electrode slurries are used to form a plurality of layers of at least one of the electrode slurries and to pulse spray at a gas pressure of 0.15 MPa to 0.3 MPa to laminate a thin film onto the object. The distance between the object and each of the nozzles is less than 70 mm. The angle of each nozzle relative to the object is less than 30 degrees, The number of pulses per second is above 10Hz. During the spraying of the electrode slurry, the object is heated to 30 to 150° C. The electrode slurries respectively include a binder, The weight ratio of the binder amount in each of the electrode slurries is 2% or less of the total solid content.

2. The method for manufacturing a storage battery according to claim 1, characterized in that: At least one of the plurality of different kinds of electrode slurries is a slurry containing a plurality of different kinds of particles.

3. The method for manufacturing a storage battery according to claim 1, characterized in that: At least one of the plurality of different types of electrode slurries is a slurry containing an active material or a main component thereof, and at least one of the plurality of different types of electrode slurries is a slurry containing a conductive agent or a main component thereof.

4. The method for manufacturing a storage battery according to claim 1, characterized in that: At least one of the nozzles uses compressed gas or liquefied gas to spray the slurry filled in the holes of the porous cylinder or the porous seamless belt rotating in the moving direction of the object in the form of particles for coating. Alternatively, at least one of the nozzles utilizes compressed gas to spray the slurry filled in a plurality of grooves formed on a rotating wide roller in the form of particles for coating.

5. The method for manufacturing a storage battery according to claim 1, characterized in that: At least one of the electrode slurries is applied by layering a plurality of nozzles arranged in a layering order in the moving direction of the object.

6. The method for manufacturing a storage battery according to claim 1, characterized in that: The storage battery is an all-solid-state battery, and any one of the plurality of different types of electrode slurries contains active material particles, electrolyte particles, and a conductive additive.

7. The method for manufacturing a storage battery according to claim 1, characterized in that: The coating is performed only on at least the interface of the object using a spray or particle generating device.

8. The method for manufacturing a storage battery according to any one of claims 1 to 7, characterized in that: The coating performed by the spray or particle generating device is to coat multiple layers on the film.